Analisis Pengaruh Instrument Landing System (ILS) untuk Peningkatan Pelayanan Keselamatan di Bandar Udara Haluleo Kendari - Driyono, Bambang; Nafkar Jaya, Muh. (Politeknik Penerbangan Makassar, 2020)
Adisucipto International Airport (JOG) has an airside area azimuth Runway (R/W) 09 category PALS (Precision Approach Lighting System) (CAT) I that occurred to be a PAPI flight navigation tool that needs to be maintained so that the slope angle (glideslope) remains at 3Â°. PAPI (Precision Approach Path Indicator) is a visual aid device that provides pilot guidance information in maintaining the aircraft's position with the correct approach at the landing point (touch down point). The results of ground inspection using an analog clinometer conducted by technicians on November 12, 2019, found a shift in the PAPI angle. The limitations of measuring instruments are an obstacle in checking the PAPI angle. The design of the PAPI angle measuring instrument is necessary to help to check before the calibration (flight inspection) every 6 months. The innovation of a digital clinometer design that combines with digital gyroscope sensor technology and adopts the purposes of an analog clinometer measuring device. The purpose of this research is to design a PAPI angle slope measurement tool with a digital display in degrees. The working principle of this tool uses a laser sensor that can measure the angle slope at a certain distance. Stages of tool design include model design, model simulation, hardware and software design, tool testing, analysis, and outcomes. The method uses functional and structural design. From the results of digital clinometer measurements and flight calibration (flight inspection) of the four boxes (A, B, C, and D), the angular deviation is still within the deviation tolerance limit, meaning that the instrument is still accurate. The conclusion is that a digital clinometer is more practical, efficient, and accurate so that this tool can support ground check testing activities at PAPI at Jogjakarta airport (JOG).